Analysis of Occlusal Stresses Transmitted to the Inferior Alveolar Nerve by Multiple Threaded Implants. Issue 11 (1st November 2013) - Sammartino, G.; Wang, Hom‐Lay; Citarella, R.; Lepore, M.; Marenzi, G.
Abstract : Background : Potential nerve injury or loss of sensation can occur after mandibular implant placement or loading. To avoid this type of damage, it is critical to determine the proper distance from implants to the mandibular nerve. Hence, the purpose of this study is to use biomechanical analyses to determine the safe distance from multiple implants to the inferior alveolar nerve. Methods: Using the boundary element method, a numerical mandibular model was designed to simulate a mandibular segment containing multiple threaded fixtures. This model allows assessment of the pressure, as induced by occlusal loads, on the trigeminal nerve. Such pressure distribution was evaluated against different distances from the fixtures to the mandibular canal, against the possible lack of the central fixture in a three‐abutment configuration, and against different levels of implant osseointegration. All the simulations considered a canal that is orthogonal to the implant axis. Results: Nerve pressure increased quickly when the implant–canal distance decreased in the range studied. Lack of the central implant to support the central abutment caused major increases in nerve pressure. Conclusions: This study suggests a minimal implant–canal distance of 1 mm to prevent inferior alveolar nerve damage caused by three connected implants. For clinical safety, an additional 0.5 mm is recommended as a cushion, so a 1.5‐mm minimal distance should be planned to avoid potential nerve injury.